Insightful Facts on Peristalsis Flow of Water Conveying Multi-Walled Carbon Nanoparticles Through Elliptical Ducts With Ciliated Walls - Ghazwani, Hassan Ali; Akhtar, Salman; Almutairi, Shahah; Saleem, Anber; Nadeem, Sohail; Mahmoud, Omar (Frontiers in Physics, 2022)
In this research, a mathematical model is disclosed that elucidates the peristaltic flow of carbon nanotubes in an elliptic duct with ciliated walls. This novel topic of nanofluid flow is addressed for an elliptic domain for the very first time. The practical applications of current analysis include the customization of the mechanical peristaltic pumps, artificial cilia and their role in flow control, drug delivery and prime biological applications etc. The dimensional mathematical problem is transformed into its non-dimensional form by utilizing appropriate transformations and dimensionless parameters. Exact mathematical solutions are computed over the elliptic domain for the partial differential equations appearing in this convection heat transfer problem. A thorough graphical assessment is performed to discuss the prime results. The graphical visualization of the flow in this elliptic duct is obtained by plotting streamlines. The viscous effects are playing a vital role in the heat enhancement as compared to the molecular conduction. Since the incrementing Brinkman number results in a declined conduction due to viscous dissipation that eventually results in an enhanced temperature profile. This research first time elucidates the impacts of nanofluid flow on the peristaltic pumping through an elliptic domain having ciliated walls. Considering water as base fluid with multi-wall Carbon nanotubes for this ciliated elliptic domain having sinusoidal boundaries.